(untitled) (Biological Sciences - PJSIR, 2002)
Preparation of polyacrylamide- sodium carboxyl methylcellulose graft having a percentage graft on level of 527.21% and graft polyacrylamide chains of 1.22 x 105 viscosity average molecular weight is described. A comparative water treatment study with particular emphasis on the flocculation potentials of the graft copolymer with alu minium sulphate, ferric sulphate and polyacrylamide using Warri River water sample is reported. The graft copolymer was not only found to exhibit relatively good flocculation characteristics but was significantly found not to impact treated water with any polymer residue. When used with aluminium sulphate in the ratio of 4:1, the turbidity of test water improved from 43.4 NIU to as low as 0.008 NIU.